Acceptability of a clofazimine tablet in children with rifampicin-resistant TB in three high-burden countries - L. Viljoen; H.R. Draper; N.T. Castillo-Carandang; N. Suryavanshi; A. Marthinus; A.M.A. Cheong; J.D.D. Ocampo; G. Dhumal; S. Bagchi; D.T. Wademan; A. Kinikar; M. Paradkar; et al. (IJTLD Open)
BACKGROUND: Rifampicin-resistant TB (RR-TB) in children is frequently treated with clofazimine (CFZ), widely available as a 100mg gel capsule. This formulation is challenging to administer and is poorly acceptable to children and caregivers. Poor acceptability may negatively impact adherence and treatment outcomes. We describe the acceptability of a novel 50mg CFZ tablet formulation among children in South Africa, India, and the Philippines. METHODS: Mixed methods assessments were completed in a moxifloxacin and CFZ safety and pharmacokinetics trial in children with RR-TB. Quantitative data were collected from 36 participants at 4 timepoints. A sub-sample of 26 child/caregiver dyads participated in ∼4 qualitative interviews. Descriptive statistics and thematic analysis were employed. FINDINGS: The median age of n=36 participants (South Africa n=20; India n=6; the Philippines n=10) was 4.9 years. The majority (29/36) received a CFZ gel capsule prior to switching to the tablet formulation. The 50mg tablet had better acceptability scores for taste (p=0.035), smell (p=0.035), and ease of swallowing (p=0.02) compared to gel capsules. Participants described the tablet formulation as easier to administer/take without a lingering smell or taste. Limited concerns were noted on staining. CONCLUSION: The novel 50mg CFZ tablet has better acceptability and should be prioritised for children wherever possible.